PRESIDEN DAN PRESIDENSIALISME: TEORI KEKUASAAN EKSEKUTIF - Kurnia, Titon Slamet (Refleksi Hukum: Jurnal Ilmu Hukum, 2024)
This article presents a comparative constitutional law study of the President's executive power. The article confidently interprets the President's executive power based on the 1945 Constitution. It does so by referring to the unitary executive theory developed in the United States by unitarians based on the Constitution of the United States. Unitary executive means that the President, as Chief Executive, holds all executive power. The study's central point is presidentialism, a system of government shared by the United States and Indonesia. This article has two purposes. First, it corrects the foundational flaw of the unitary executive theory developed by unitarians because they do not specifically claim presidentialism as the underlying principle of their theory. Second, it makes the unitary executive theory applicable to Indonesia.